Gestational diabetes and postnatal depressive symptoms: A prospective cohort study in Western China - Mak, J.; Lee, A.; Pham, N.; Tang, L.; Pan, X.; Lee, Andy; Sun, X. (Elsevier BV, 2018)
© 2018 Australian College of Midwives Background: Gestational diabetes mellitus (GDM) can lead to adverse birth outcomes, but its effect on postnatal depression has not been thoroughly investigated, especially in Asian populations. Aim: To determine the prospective association between GDM and postnatal depressive symptoms in Western China. Methods: A prospective cohort study of 1449 mothers was conducted in Chengdu, capital city of Sichuan Province. GDM was diagnosed during pregnancy using oral glucose tolerance tests. Maternal depressive symptoms were measured at 32–37 weeks of gestation, then at one and three months after giving birth using a validated Chinese version of the Edinburgh Postnatal Depression Scale (EPDS). Associations between the postnatal EPDS scores, GDM status and blood glucose levels were assessed by multivariable mixed-effects regression models, accounting for baseline EPDS scores of the cohort and other confounding factors. Findings: Compared to the non-GDM group (n = 1220), women with GDM (n = 229, 15.8%) reported significantly higher mean EPDS scores at both 1-month (p = 0.02) and 3-month (p < 0.01) postpartum. Similarly, high levels of fasting, 1-h and 2-h blood glucose levels during pregnancy were associated with increased EPDS scores. Mixed-effects models further confirmed the positive association between GDM status and postnatal depressive symptoms, even though the mean EPDS scores decreased substantially over the three time points. Conclusion: Chinese women with GDM were more susceptible to postnatal depression than others without the condition, despite their depressive symptoms reducing over time after childbirth. It is thus important to raise awareness of postnatal depression amongst healthcare professionals who care for women with GDM.